Exploring the feasibility of a culturally tailored infant nutrition intervention: a qualitative study of perspectives from community facilitators and attendees in a pilot randomised controlled trial - Nurture Early for Optimal Nutrition (NEON) in East London - Edward Fottrell; Michelle Heys; Gary Tse; Oyinlola Oyebode; Mitch Blair; Monica Lakhanpaul; Logan Manikam; Dianna Smith; Audrey Prost; Neha Batura; Atul Singhal; Lisa Dikomitis; et al. (BMJ Publishing Group, 2024)
Introduction Appropriate and healthy feeding practices can enhance a child's health, prevent obesity and reduce chronic metabolic disease risks. Given the ethnic variations in feeding practices and metabolic risk, interventions must be community specific. Culturally tailored grassroots interventions targeting infant feeding can induce behavioural changes, mitigating chronic metabolic disease risks in later life.The aim of this study was to explore participant feedback and inform intervention delivery methods within marginalised communities.Methods A pilot three-arm cluster randomised controlled trial was conducted in the Tower Hamlets and Newham boroughs of London, involving community participatory learning and action groups. The study recruited 186 South Asian (Indian, Bangladeshi, Pakistani and Sri Lankan) mothers or carers of children aged 0-2 years. Participants in intervention arms were invited to either face to face or online intervention arms, facilitated by trained multilingual community facilitators (CFs), offering culturally informed discussions on child nutrition and care practices. The qualitative study was embedded within this trial, collecting feedback through interviews and focus groups. Thematic analysis was employed to identify key themes, focusing on intervention fidelity and acceptance.Results Of the initial attendees, 42 (from the remaining 153 at the study's conclusion) and 9 CFs offered feedback on the intervention's delivery and suggestions for enhancing community-based interventions' success. Key findings highlighted the need for a more flexible approach to boost participation and the significance of providing accessible, translated documents and resources. Participants expressed a strong preference for a hybrid model of intervention delivery, combining face-to-face and online sessions to accommodate diverse needs.Conclusion Parenting interventions, particularly for new mothers, may engage more of the target population by adopting a hybrid design. This would provide attendees with the flexibility to select the delivery method, session timings and the option to participate at any stage of the intervention. The study underscores the importance of cultural tailoring and flexible delivery methods in enhancing participation and engagement in community-based health interventions.